"Seeking Refuge in God against God": The Hidden God in Lutheran Theology and the Postmodern Weakening of God - Stopa, Sasja Emilie Mathiasen (Open theology, 2018)
Martin Luther emphasizes the affective experience of the living God rather than God as an abstract, metaphysical idea. Luther explains this experience of God by distinguishing between God as Deus absconditus in his hidden majesty and God as Deus revelatus suffering on the cross. According to Luther, sinners experience the hidden God as a terrifying presence causing them to suffer. Through faith, however, sinners are able to recognize that this wrathful God is one with the God of love and mercy revealed in Christ. Based on this paradoxical understanding of God, Luther admonishes Christians to seek refuge in God against God. In recent decades, Luther’s accentuation of the revealed God has inspired postmodern philosophers and theologians in their efforts to recast the notion of God in light of the Nietzschean outcry on the death of God and Heidegger’s critique of ontotheology. Hence, John D. Caputo and Gianni Vattimo have weakened the notion of an omnipotent God in favour of an anti-metaphysical understanding of "god" kenotically denouncing his power and occurring as an ethically obliging event. Conversely, postmodern thinking have inspired contemporary Lutheran theologians to reinterpret the notion of God. In this article, Luther’s theology serves as a resource for critiquing these postmodern attempts at post-metaphysically rethinking God the central claim being that they are unable to proclaim the saving promise of a reconciliatory union between God hidden and revealed and between sinful human beings and Christ. As a result, theology is reduced to an ethical manifesto or to compassionate anthropology leaving despairing humans without a language with which to express their sufferings.